1978
DOI: 10.1002/mpo.2950040211
|View full text |Cite
|
Sign up to set email alerts
|

Nonbacterial thrombotic endocarditis in cancer patients: Comparison of characteristics of patients with and without concomitant disseminated intravascular coagulation

Abstract: Thirty-one cases with malignant neoplasm and nonbacterial thrombotic endocarditis (NBTE) were studied. A threefold increase in the incidence of NBTE over the five-year period ending in 1976 was noticed. Seventy-one percent of patients with NBTE had concomitant disseminated intravascular coagulation (DIC). Adenocarcinomas of the lung or ovary were the most common tumors (48%), followed by hematologic malignancies (25%). Five patients had acute leukemia, two of whom had received bone marrow transplantation. Sudd… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

1981
1981
2011
2011

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…2,5 Adenocarcinomas of the lung and ovary comprise nearly 50% of the cases, followed by hematologic malignancies that account for 25%. [5][6][7][8] Therefore, when evaluating patients with NBTE without a clear etiology, an occult neoplasm must be excluded.…”
mentioning
confidence: 99%
“…2,5 Adenocarcinomas of the lung and ovary comprise nearly 50% of the cases, followed by hematologic malignancies that account for 25%. [5][6][7][8] Therefore, when evaluating patients with NBTE without a clear etiology, an occult neoplasm must be excluded.…”
mentioning
confidence: 99%
“…Lastly, Sharma et al [33] described fatal cerebral embolization from NBTE in a patient with major trauma, adult respiratory distress syndrome, sepsis, and DIC. In a series of 31 patients with NBTE and cancer reported by Bedikian et al [1], there was a 64.5% incidence of pneumonia. The immediate cause of death was pneumonia in 34.5% of the cases, and chronic pulmonary failure in 12.9%.…”
Section: Resultsmentioning
confidence: 96%
“…Kim et al [19] found histologic evidence of DIC in 50% of patients with NBTE in their autopsy series. Bedikian et al [1] found histologic evidence of DIC in 71% of their patients with NBTE and cancer. However, a prospective study of cancer patients by Edoute et al [9] found no statistically significant increase in the incidence of Ddimer elevation among patients with valvular vegetations compared with those without vegetations.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Among cancer patients, adenocarcinoma is by far the most common histological subtype. Some case series have also reported an association with hematologic malignancies, particularly leukemia [ 12 , 13 ].…”
Section: Discussionmentioning
confidence: 99%